Two syringes technique for spinal anesthesia to prevent hypotension in patients undergoing elective cesarean section - Shrestha, Saurav; Pokhrel, Jeju Nath; Gurung, Tara; Devkota, Sagar; Sharma, Apurb (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To compare the incidence of hypotension after intrathecal administration of hyperbaric bupivacaine and fentanyl in two different syringes against standard injection of mixed fentanyl with hyperbaric bupivacaine. Methods: This was a prospective comparative study conducted in 174 parturients undergoing elective caesarean section at Paropakar Maternity & Women’s Hospital. Hemodynamic effects and characteristics of block were monitored and recorded and compared between the two groups, group S (single syringe) and group D (double syringe). Results: The incidence of hypotension was almost similar in the two groups but the drop in systolic blood pressure and mean arterial pressure at 5 minutes and 7.5 minutes after subarachnoid block was significant in group S as compared to group D (p<0.005 and p<0.005 respectively). Conclusion: Hyperbaric bupivacaine with fentanyl, which when injected separately without mixing, is associated with lesser incidence of hypotension following subarachnoid block.